Replication-incompetent rabies virus vector harboring glycoprotein gene of lymphocytic choriomeningitis virus (LCMV) protects mice from LCMV challenge. - Mutsuyo Takayama-Ito; Chang-Kweng Lim; Yukie Yamaguchi; Guillermo Posadas-Herrera; Hirofumi Kato; Itoe Iizuka; Md Taimur Islam; Kinjiro Morimoto; Masayuki Saijo (Public Library of Science (PLoS), 2018)
BACKGROUND:Lymphocytic choriomeningitis virus (LCMV) causes a variety of diseases, including asymptomatic infections, meningitis, and congenital infections in the fetus of infected mother. The development of a safe and effective vaccine against LCMV is imperative. This study aims to develop a new candidate vaccine against LCMV using a recombinant replication-incompetent rabies virus (RV) vector. METHODOLOGY/PRINCIPAL FINDINGS:In this study, we have generated a recombinant deficient RV expressing the LCMV glycoprotein precursor (GPC) (RVΔP-LCMV/GPC) which is lacking the RV-P gene. RVΔP-LCMV/GPC is able to propagate only in cells expressing the RV-P protein. In contrast, the LCMV-GPC can be expressed in general cells, which do not express RV-P protein. The ability of RVΔP-LCMV/GPC to protect mice from LCMV infection and induce cellular immunity was assessed. Mice inoculated intraperitoneally with RVΔP-LCMV/GPC showed higher survival rates (88.2%) than those inoculated with the parental recombinant RV-P gene-deficient RV (RVΔP) (7.7%) following a LCMV challenge. Neutralizing antibody (NAb) against LCMV was not induced, even in the sera of surviving mice. CD8+ T-cell depletion significantly reduced the survival rates of RVΔP-LCMV/GPC-inoculated mice after the LCMV challenge. These results suggest that CD8+ T cells play a major role in the observed protection against LCMV. In contrast, NAbs against RV were strongly induced in sera of mice inoculated with either RVΔP-LCMV/GPC or RVΔP. In safety tests, suckling mice inoculated intracerebrally with RVΔP-LCMV/GPC showed no symptoms. CONCLUSIONS/SIGNIFICANCE:These results show RVΔP-LCMV/GPC might be a promising candidate vaccine with dual efficacy, protecting against both RV and LCMV.